The Commoditization of Ecosystems within Chile's Mapuche Territory: A Violation of the Human Right to Health - Marcela Castro Garrido; Ana María Alarcón (Harvard FXB Center for Health and Human Rights, 2023)
The Araucanía region of Chile is characterized by a significant rural Indigenous population-the Mapuche people-who preserve their cultural beliefs about the world around them. This region is also distinguished by the conflict between the Mapuche people and the Chilean government. The Chilean state has supported the development of extractive projects such as industrial plantations, hydroelectric plants, and aquaculture, using nature to generate profits. This has collided with the Mapuche's inextricable relationship with nature and territory, which they value as a spiritual and historical space. Our qualitative study, conducted between 2016 and 2019 in three Araucanía territories with large Mapuche populations, sought to explore Mapuche perceptions of nature, their right to health, Indigenous rights generally, and Indigenous communities' relationship with the state. The results show an overall perception among Mapuche communities of an extractive mentality at the heart of the Chilean state, regardless of the administration in power, as well as a belief that the industrial occupation of their territories represents a process of colonialism and the transgression of ancestral rights. This extractivist approach by the state has caused Mapuche communities to witness enormous changes to their ecosystem, with negative impacts on their well-being.